STRATEGI GURU PAI DALAM MENANGGULANGI PERILAKU INTOLERENSI DILINGKUNGAN SEKOLAH - Silvia Indah Lestari; Aliqma Mutiara Zamil; Lutfiatul fawaida; Ema Sulistia Ningsih (STKIP Subang, 2025)
This study aims to examine the role of Islamic Religious Education (IRE) teachers in preventing intolerant behavior among students. The article employs a descriptive-analytical approach and thematic interpretation in its literature review. The research focuses on several relevant written documents, particularly those discussing the role of Islamic Religious Education in preventing intolerance. Secondary sources, such as books, journals, and other written materials, are also utilized to gain deeper insights, facts, and analyses. The data is analyzed using content analysis methods, allowing the researcher to describe and connect the data with supporting documents related to Islamic Religious Education. Through this analysis, the findings show that IRE teachers play a strategic role in preventing intolerance by teaching Islamic values such as tolerance, justice, and mutual respect. Teachers act as role models in shaping inclusive student character and integrating extracurricular activities to promote harmony. The study concludes that Islamic Religious Education (IRE) teachers hold a crucial role, especially in forming students' character and personality based on noble Islamic values. They are not only responsible for teaching the theoretical aspects of religion but also serve as moral and spiritual exemplars who teach noble character, justice, and anti-intolerance behavior in education. The value of tolerance is taught to students with the hope that they will grow into wise individuals rooted in moral and religious values.